Shear and laser cutting effects on hydrogen embrittlement of a high-Mn TWIP steel. (January 2020) - Sheng, Zhendong; Guo, Xiaofei; Prahl, Ulrich; Bleck, Wolfgang
Highlights: TWIP steel processed by laser was insensitive to hydrogen embrittlement (HE). TWIP steel processed by shearing significantly degraded the HE resistance. Shear-affected zone from the shear-cut specimen facilitated the formation of a flat triangle area on fracture surface. Abstract: The influence of shear and laser cutting on hydrogen embrittlement of a hot-rolled Fe-18Mn-0.4C-1.2Al-1.8Cr TWIP (twinning induced plasticity) steel sheet in 3 mm thickness was investigated by hydrogen pre-charging and subsequent slow strain rate tests. Due to the severe plastic deformation during shearing, the ductility of the shear-cut specimen was significantly reduced in tensile test compared to the laser-cut specimen. After hydrogen pre-charging, the laser-cut specimen exhibited less susceptibility to hydrogen embrittlement than the shear-cut specimen. The fractographic analysis revealed that the shear-affected zone acted as crack initiation site during tensile test, which exhibited a flat fracture zone with high stress triaxiality. In hydrogen-charged condition, the flat fracture zone transited from large primary dimples to the mixed features with dimples and quasi-cleavage features.